A secure and effective cross domain anonymous authentication scheme for highway network toll collection system - Jing Chen; Tao Li; WenJiang Liu; Hao Li (Alexandria Engineering Journal, 2025)
In today's accelerating process of global economic integration and urbanization, highways have become important indicators for measuring national or regional economic development and social progress in terms of their construction and operation levels. With the expansion of the highway network, highway network toll collection system (HNTCS) faces the challenge of balancing toll efficiency with user privacy and data security. Especially for cross domain authentication, traditional centralized authentication methods suffer from single point of failure and privacy leakage issues, and are difficult to meet the growing demand for authentication. Therefore, this article proposes a cross-domain authentication scheme for HNTCS based on two factors, which not only enables smooth passage of cross domain vehicles between different charging domains, but also effectively protects user privacy and data security. The scheme achieves efficient key negotiation, avoids the risk of privacy leakage and ensures the security of the transmission process. Analysis shows that this scheme can effectively resist security attacks and has low costs.